2021
DOI: 10.1097/pq9.0000000000000430
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinating in the Emergency Department, a Model to Overcome Influenza Vaccine Hesitancy

Abstract: Introduction: Vaccine hesitancy and delays in vaccine administration time have limited the success of prior influenza vaccination initiatives in the pediatric emergency department (ED). In 2018–2019, season 1, this ED implemented mandatory vaccine screening and offered the vaccine to all eligible patients; however, only 9% of the eligible population received the vaccine. In 2019–2020, season 2, the team sought to improve influenza vaccination rates from 9% to 15% and administer over 2,000 vaccines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Questions included information about the respondent and their primary ED (including the respondent’s role, the ED’s annual volume, location, and the proportion of patients receiving government insurance), whether the ED offers CVs, and how many vaccines were administered in the past year. Facilitators and barriers were assessed via the question: “Which of the following do you perceive to be [facilitators/barriers] of COVID-19 vaccination to children in your ED?” using a 5-point Likert scale and a list of potential facilitators and barriers, which were selected based on the prior literature as well as a priori by the investigators and their prior research in this area [ 26 , 35 , 39 , 46 ]. Additional questions assessed (1) the desire to collaborate to start or improve a CV program and (2) the desire to participate in future focus groups related to barriers and facilitators of vaccine programs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Questions included information about the respondent and their primary ED (including the respondent’s role, the ED’s annual volume, location, and the proportion of patients receiving government insurance), whether the ED offers CVs, and how many vaccines were administered in the past year. Facilitators and barriers were assessed via the question: “Which of the following do you perceive to be [facilitators/barriers] of COVID-19 vaccination to children in your ED?” using a 5-point Likert scale and a list of potential facilitators and barriers, which were selected based on the prior literature as well as a priori by the investigators and their prior research in this area [ 26 , 35 , 39 , 46 ]. Additional questions assessed (1) the desire to collaborate to start or improve a CV program and (2) the desire to participate in future focus groups related to barriers and facilitators of vaccine programs.…”
Section: Methodsmentioning
confidence: 99%
“…Facilitators and barriers were assessed via the question: "Which of the following do you perceive to be [facilitators/barriers] of COVID-19 vaccination to children in your ED?" using a 5-point Likert scale and a list of potential facilitators and barriers, which were selected based on the prior literature as well as a priori by the investigators and their prior research in this area [26,35,39,46]. Additional questions assessed (1) the desire to collaborate to start or improve a CV program and (2) the desire to participate in future focus groups related to barriers and facilitators of vaccine programs.…”
Section: Survey Development and Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…ED caregivers were chosen because prior work by this study team as well as others demonstrated that children without a medical home and those from vulnerable groups (especially children age 0-5yr and those from low-income households) tend to have disproportionately high rates of ED use, thus both the Centers for Disease Control and Prevention (CDC) as well as the World Health Organization recognize the ED as an important site for engagement in vaccination efforts. [23] , [24] , [25] , [26] , [27]…”
Section: Introductionmentioning
confidence: 99%
“…As such, EDs are recognized as key targets to increase COVID-19 vaccination rates. [1][2][3] Despite an abundance of COVID-19 vaccination clinics, barriers such as vaccine hesitancy, lack of transportation, transient housing, mental health disorders, and difficulty in making an appointment have impacted vaccination rates in underserved populations. The American College of Emergency Physicians (ACEP) postulated that "rising ED volumes continue to include a disproportionately increasing underserved, uninsured and minority population [who are] less likely to have had adequate preventive and primary care access and are more likely to be under-immunized."…”
mentioning
confidence: 99%